INTERPRETING CHANGES IN ALBEDO AND MASS BALANCE AT WHITE GLACIER, CANADIAN ARCTIC ARCHIPELAGO - Y. Ye; Y. Tian (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2022)
Alpine glaciers are sensitive to changes in land surface temperature (LST), and measurements of the mass balance are limited, especially for small glaciers. In this study, we investigate the relationship between snow albedo of the melting season (June, July, and August) and annual glacier mass balance of the White Glacier from 2002 to 2018. Since there are many gaps in the albedo data, we use a interpolation method to fill them and then obtain the average value of the melting season. The study results show that surface temperature plays a dominant role in albedo and mass balance changes, and mass balance change and albedo variation show a significant consistency, with an excellent correlation (R 2 > 0.93). The acceleration of mass balance shows that the rate of mass reduction slows down, and the albedo change shows that the albedo increases from year to year. The interpolation albedo measurements using MODIS data can provide a useful means to reflect the annual change of glacier mass balance.